Risk management of the implementation of work health safety in radiology - SHOLIHAH, Q.; KUNCORO, W.; SARI, R. A; LUKODONO, R. P; SWARA, S. E (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTThe high use of radiation for medical activities is the second largest contribution the radiation source that we receive, which in addition to providing benefits, can also cause harm for radiation workers, the community, and the surrounding environment. The purpose of this study was to analyze the application and implementation of radiation safety at the Installation Radiology of UNISMA Hospital in Malang. Descriptive research was conducted with a qualitative approach. It is known that 20% of hazards are in a low category; 30 % of hazards are in the moderate category, 50% are in the high category.RESUMENEl alto uso de radiación para actividades médicas es la segunda contribución más importante de la fuente de radiación que recibimos, que además de proporcionar beneficios, también puede causar daños a los trabajadores de radiación, la comunidad y el entorno circundante. El propósito de este estudio fue analizar la aplicación e implementación de la seguridad radiológica en la Instalación de Radiología del Hospital UNISMA en Malang. La investigación descriptiva se realizó con un enfoque cualitativo. Se sabe que el 20% de los peligros están en una categoría baja; El 30% de los peligros están en la categoría moderada y el 50% están en la categoría alta.